Infographic. Doping without drugs: how para-athletes may self-harm to boost performance - Gee, C. M.; Nightingale, T. E.; West, C. R.; Krassioukov, A. V. (British Journal of Sports Medicine, 2021)
This infographic provides a summary of the use of boosting by athletes with spinal cord injury (SCI); its causes, warning signs and dangers, and the current approach of the International Paralympic Committee (IPC) to testing.